354 HLA ASSOCIATIONS WITH T CELL REACTIVITY TO TYPE II COLLAGEN EPITOPES IN PATIENTS WITH RHEUMATOID ARTHRITIS. (10th December 2015) - Postlethwaite, A. E.; Seyer, J. M.; Endres, R.; Ward, F.; Kang, A. H.; Myers, L.; McKown, K.; Barrow, K.; Carbone, L.
Abstract : A set of shared epitope alleles at the B1 locus of the HLA-DR region, HLA DRB 1 *0101, *0401, *0404, *0405, *1001, *1402, are highly associated with rheumatoid arthiritis (RA), while HLA-DRB1 alleles *0103, *0402, *1102, *1103, *1301, *1302 are protective. This link between arthritis susceptibility and HLA class II expression has reinforced the view that RA is, at least in its early phases, likely a T cell-mediated immunospecific disease. Since DR1 (DRB*0101) and DR4 (DRB1*0401) transgenic mice develop polyarthritis when immunized with human (H) type II collagen (CII), we wanted to determine whether certain cyanogen bromide (CB) fragments of H CII would elicit interferon (IFN)-γ production by RA PBMC and whether intensity of the IFN-γ response would correlate with certain HLA-DRB1, -DQA and/or DQB alleles. Peripheral blood mononuclear cells (PBMC) were collected from 102 patients with RA in various stages of disease and on conventional therapies and set up in culture with purified CB peptides derived from H CII. Aliquots of PBMC were subjected to HLA-DRB1, DQA1 and DQB1 typing. After 6 days culture, IFNγ levels were quantitated by ELISA. Analysis of variance was used to determine the association of HLA haplotypes with levels of IFN-γ produced in cultures of PBMC with H CII CB peptides. RA patients with shared epitope as a group had higher IFN-γ production to HCB8 compared with those patients without the shared epitope. RA patients with any one of the DRB1 protective alleles had higher IFN-γ production to HCB9. Higher IFN-γ production to CB peptides was observed with the following DRB1 alleles: DRB1 *0401' HCB11; DRB1 *0408 'HCB6 and HCB12; DRB1 *1302 'HCB8 and HCB9; DRB1 *1303 'HCB11; DRB1 *1401 'HCB6, HCB9, and HCB10. Patients who were DQ3 positive had higher IFN-γ production to HCB11 while no CB peptides elicited higher responses in DQ5 patients. These studies suggest that HLA DR and DQ alleles determine to which epitopes in H CII patients with RA develop T cell immunity. Supported by an RA SCOR NIAMS, and Department of Veterans Affairs, USA, NIH General Clinical Research Center at the University of Tennessee, Memphis, and a grant from Fibrogen Corporation.